2011
DOI: 10.1039/c0cp02228d
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of excited-state tautomerization in single molecules

Abstract: Tautomerism process of single fluorescent molecules was studied by means of confocal microscopy in combination with azimuthally or radially polarized laser beams. During a tautomerism process the transition dipole moment (TDM) of a molecule changes its orientation which can be visualized by the fluorescence excitation image of the molecule. We present experimental and theoretical studies of two porphyrazine-type molecules and one type of porphyrin molecule: a symmetrically substituted metal-free phthalocyanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…3(a), was 20 nm from the nanowire surface. This height of the particle corresponded to the stack of twenty TPP molecules, which was estimated from the π-π intermolecular distance 28) and the thickness of the TPP molecule 29) , assuming that planar-shaped TPP molecules were stacked on the nanowire in parallel to the surface plane 30) .…”
Section: Current and Noise In Nanowire With Tpp Particlementioning
confidence: 99%
“…3(a), was 20 nm from the nanowire surface. This height of the particle corresponded to the stack of twenty TPP molecules, which was estimated from the π-π intermolecular distance 28) and the thickness of the TPP molecule 29) , assuming that planar-shaped TPP molecules were stacked on the nanowire in parallel to the surface plane 30) .…”
Section: Current and Noise In Nanowire With Tpp Particlementioning
confidence: 99%
“…[19] A further twist on such approaches can be realized by exciting the molecule with azimuthally or radially polarized doughnut modes. [20] Due to the scanning nature of all these techniques they are not well suited for detecting many molecules in parallel, which makes them non-ideal for incorporation into single-molecule super-resolution imaging (see Section 2).…”
Section: Introductionmentioning
confidence: 99%
“…10 This suggests a much slower rate of tautomerization for isolated H 2 Pc molecules. However, an early attempt to use fluorescence microscopy to visualize the ETDMs of single H 2 Pcs embedded into polymers or attached to silica failed, 17 presumably because of the low rate of image acquisition (B100 s) compared with the rate of tautomerization. In this study, we report the real-time visualization of the ETDMs of single H 2 Pcs using defocused wide-field microscopy at a temporal resolution of 100 ms. [18][19][20][21][22][23] We found that a H 2 Pc derivative shows slow tautomerization at an air/octadecyl-group-modified glass interface, which is consistent with previous DFT calculations.…”
mentioning
confidence: 99%